2018
DOI: 10.1096/fj.201800407rr
|View full text |Cite
|
Sign up to set email alerts
|

Lack of p11 expression facilitates acidity‐sensing function of TASK1 channels in mouse adrenal medullary cells

Abstract: External acidity induces catecholamine secretion by inhibiting TASK1-like channels in rat adrenal medullary (AM) cells. TASK channels can function as a heteromer or homomer in the TASK subfamily. In this study, we elucidate the molecular identity of TASK1-like channels in mouse AM cells using gene knockout. Genetic deletion of TASK1, but not TASK3, abolished the depolarizing inward current and catecholamine secretion in response to acidity, whereas it did not affect the resting current level. Immunocytochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…TWIK-related acid-sensitive K + (TASK) channels contribute to the resting membrane potential in a variety of cells, such as carotid body (CB) glomus cells, 1 brain neurons, 2,3 and endocrine cells. 48 They belong to the two-pore domain K + (K 2P ) channel family, 9,10 which comprises 15 subunits in humans. Having two pore domains in each subunit, K 2P channels exist as a homodimer or heterodimer of subunits.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…TWIK-related acid-sensitive K + (TASK) channels contribute to the resting membrane potential in a variety of cells, such as carotid body (CB) glomus cells, 1 brain neurons, 2,3 and endocrine cells. 48 They belong to the two-pore domain K + (K 2P ) channel family, 9,10 which comprises 15 subunits in humans. Having two pore domains in each subunit, K 2P channels exist as a homodimer or heterodimer of subunits.…”
Section: Introductionmentioning
confidence: 99%
“…The TASK subfamily consists of TASK1, TASK3, and TASK5: TASK1 and TASK3 function as homomeric or heteromeric channels, 11,12 whereas TASK5 is devoid of channel activity in exogenous expression systems. 13 The molecular structure of TASK channels constitutively expressed in some cells 7,12,14,15 or exogenously expressed in oocytes 16 or cell lines 3,11 has been investigated with biochemical or electrophysiological approaches. Single-channel analysis in mouse 12 and rat CB glomus cells 14 revealed that most of the TASK channels are heteromeric TASK1-TASK3 structures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ionic mechanisms for muscarinic receptor-mediated excitation in AM cells differ among species of mammals, and their details have not yet been sufficiently elucidated (Inoue et al, 2018). In rat AM cells, muscarinic M 1 receptor (also known as Chrm1) stimulation (Harada et al, 2015) induces the endocytosis of TASK1 (also known as Kcnk3) channels with a consequent decrease in K + channel activity Matsuoka and Inoue, 2017;Inoue et al, 2019b), whereas in guinea pig AM cells the muscarinic receptor-mediated excitation is ascribed to not only TASK1 channel inhibition, but also to nonselective cation (NSC) channel activation (Inoue and Kuriyama, 1991;Inoue et al, 2012). This muscarinic receptorregulated NSC channel has reversal potential of 0 mV and exhibits a conductance decrease at membrane potentials below −50 mV: i.e.…”
Section: Introductionmentioning
confidence: 99%